Pilot-scale biomass gasification system for hydrogen production from palm kernel shell (part B): dynamic and control studies - Hussain, M. (Springer Science and Business Media Deutschland GmbH, 2021)
This paper aims to contribute toward the understanding of the dynamics and control of the biomass gasification process utilizing palm kernel shell (PKS) as the feedstock. In this paper, dynamic modeling of a PKS steam gasification of an integrated biomass pilot plant in Universiti Teknologi PETRONAS (UTP) is developed using Aspen PlusÂ®. A 2 Ã 2 linear model predictive controller (MPC) scheme is implemented and compared against the conventional Proportional-Integral (PI) controller, where the linear MPC controller is interfaced with the Aspen Plus model of the pilot plant. Pseudorandom binary sequence (PRBS) signals with different signal bandwidths are used to excite the biomass gasification system for the open-loop model identification. The system is investigated with 2.5, 5, and 10 step changes in the controlled variables. Quantitative analysis for the performances of the PI and MPC controllers in their ability to track the setpoint of both the controlled variables based on the Integral Absolute Error (IAE) performance index is performed. It can be observed that, for the biomass gasifier studied, both the PI and MPC controllers are relatively comparable in terms of their performances under the step changes introduced. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.